2022
DOI: 10.1016/j.jvs.2021.07.243
|View full text |Cite
|
Sign up to set email alerts
|

Natural history, growth rates, and treatment of popliteal artery aneurysms

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Interestingly, data on the association between intraluminal thrombus and patent outflow vessels are scarce, despite an obvious connection [28]. Future studies taking into account the aneurysm volume, i.e., thrombus/lumen ratio, could help to broaden the indicatory spectrum in an analogy to AAA, where the aneurysm volume, regardless of ILT, has been suggested to be a more reliable indicator of future repair [9,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, data on the association between intraluminal thrombus and patent outflow vessels are scarce, despite an obvious connection [28]. Future studies taking into account the aneurysm volume, i.e., thrombus/lumen ratio, could help to broaden the indicatory spectrum in an analogy to AAA, where the aneurysm volume, regardless of ILT, has been suggested to be a more reliable indicator of future repair [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…This approach is currently being investigated to provide better evidence [2,8]. A smaller diameter (<15 mm) upon first diagnosis is associated with more frequent subsequent emergent repairs [8,9]. In general, the annual growth rate varies among individual patients and ranges between 0.7 and 6.5 mm/year, depending on the initial diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The SVS guidelines focus mainly on quantifying and reporting PAA size [ 7 ]. However, size alone does not singularly dictate the need for operative repair; studies have demonstrated that thrombus burden and the percent of thrombus also portends a high risk of thromboembolic events and amputation [ 4 , 40 , 41 , 42 ]. Manual segmentation of the vessel lumen to identify these high-risk features is difficult given the similar echogenicity of adjacent plaques.…”
Section: Discussionmentioning
confidence: 99%
“…The latter under the pressure of the cardiac systole can embolize and distally occlude the arteries that originate from the popliteal (tibial vessels) or even, if the thrombus is small, the arterioles of the foot with a phenomenon called ‘microembolization’ [ 68 ]. In these cases, the clinical onset is pain, pallor and hypothermia of the leg or foot because the embolus has produced a reduction in the vascularization of the limb with a consequent picture of ischaemia that will be more or less severe depending on the distal vessels involved [ 69 , 70 ]. The standard treatment for this pathology involves performing a surgical bypass to drain the haematoma and restore the blood supply to the foot.…”
Section: Clinical Applications Of Covered Stentsmentioning
confidence: 99%